Earnings management surrounding CEO turnover: evidence from Chinese listed firms - CHEN, sisi (2016)
This paper examines the effects of CEO turnovers on earnings quality of Chinese listed firms. CEO turnover can be classified into two types that are respectively routine and non-routine CEO change and external and internal successors. After various selection procedures, modified Jones model and a multivariate regression are respectively applied to calculate the discretionary accruals and test hypothesis proposed. According to empirical results, non-routine CEO change is associated with more earning management and lower earnings quality, and external successors are associated with less earning manipulation thus higher earnings quality. In addition, more earning management in the transition year can be found than that in the following year.